Transformasi Digital dan Manajemen SDM di Masa Depan Kerja: Tinjauan Sistematis terhadap Inklusivitas dan Keberlanjutan - Anisa Sal Sabilla Putri; Salwa Putri Qomariyah; Rafika Meilia Sari (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
Digital transformation in Human Resource Management (HRM) has shifted the organizational paradigm from an administrative function to a strategic function focused on adaptive and sustainable human resource development. This study aims to systematically review the integration of digital technology in HRM practices with particular emphasis on inclusivity and organizational sustainability. The method employed is a literature review analyzing various studies related to the implementation of Artificial Intelligence (AI), big data analytics, and digital systems in recruitment, competency development, and employee performance evaluation. The findings indicate that digital transformation enhances operational efficiency, decision-making quality, and workplace flexibility. However, the adoption of digital technology also creates ethical challenges, including algorithmic bias, unequal access to technology, and concerns regarding employee data privacy. Therefore, the implementation of Equity, Diversity, and Inclusion (EDI) principles is essential in developing fair and inclusive HRM systems. Furthermore, continuous learning cultures and flexible work models have proven effective in supporting employee well-being while strengthening organizational resilience in facing global changes. This study emphasizes the importance of synergy between technological innovation, ethical leadership, and sustainability in building HRM systems that are responsive to the future of work.